Romantic knits : 16 knitting patterns for blouses, cardigans and other elegant knitwear - Arnesen, Helene (Page Street Pub Co, 2025)
Fill your wardrobe with breathtaking handmade pieces that you will treasure for years to come. Knitwear designer Helene Arnesen is a master in combining simple knitting techniques with elegant details, such as billowing sleeves, ribbon ties and lace edging, to capture the romantic essence of vintage fashion. More than just a collection of practical patterns, this thoughtfully and artistically crafted book will evoke inspiration and delight with each turn of the page. With Helene, a world of beautiful feminine charm is only a knit purl away.